Towards Real-time Score Analysis in PWGL - Kuuskankare, Mika (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2021.19424, 2021)
In this paper, we introduce an original approach to computerized music analysis within the graphical computer-assisted composition environment called PWGL. Our aim is to facilitate the realtime analysis of interactive scores written in common Western music notation. To this end, we have developed a novel library that allows us to analyze scores realized with the help of ENP (the graphical music notation module of PWGL), and to visualize the results of the analysis in realtime. ENP is extended to support the display of supplementary information that can be drawn on top of the score as an overlay. The analysis backend is realized with the help of our builtin musical scripting language based on pattern matching. The analysis results are presented directly as a part of the original score leveraging the extensible and interactive visualization capabilities of ENP. In this paper we describe the current state of the library and present, as a case study, a fully functional application allowing for the realtime analysis and display of voice leading errors according to the counterpoint rules developed mainly in the Renaissance and Baroque eras.